Tinjauan Yuridis Terhadap Tindak Pidana Pemalsuan Asal-Usul Seorang Anak dalam Putusan Perceraian - I Made Mudana Adi Putra; Anak Agung Sagung Laksmi Dewi; Luh Putu Suryani (Jurnal Analogi Hukum, 2022)
Counterfeiting committed by the medical personnel if the contents of the medical record contain some or all of the contents that are changed or made differently from medical actions carried out by the doctors or medical teams, it will have an adverse effect and even create disputes between the patient's family, and lead it into unclear identity. The formulations of the problem of this research are How is the legal regulation of the counterfeiting crime against the origin of a child? What are the criminal sanctions for counterfeiting the origin of a child when a divorce occur? This research has purpose is to find out the arrangements of legal for the counterfeiting crime of a child's origins and criminal sanctions against counterfeiting a child's origins a divorce occur. The benefits of this research can be used as a source of input, especially regarding the juridical review in divorce verdict. regulated in Law 36 of 2014 concerning 2014 Health Workers. contained in Article 84 which contains actions that occur due to negligence. The rules of origin, although not explicitly stated in the form of identity falsification or the origin of the child, are regulations related to falsification. The sanction for falsification of intentionally embezzling a person's origins is punishable by embezzlement of origin with a maximum imprisonment of six years.